(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article presents the degree of supply of humus and nutrients in the genetic layers of grassland-gray soils distributed in the gray-oasis areas. Quantitative indicators of humus reserves in irrigated meadow-gray soils of Shurchi district in the 0-50 cm layer fluctuate at short intervals, in the upper 0-30 cm layer 60,90 tons per hectare, nitrogen 5,29 tons, phosphorus 31,20 tons, potassium 84,00 tons and the amount of total salts and ions with different levels of salinity, depending on soil-climatic and humaneconomic conditions.